Factors associated with lingual tonsil hypertrophy in Canadian adults - Matthew S. Harris; Brian W. Rotenberg; Kathryn Roth; Leigh J. Sowerby (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Hypertrophy of the lingual tonsil tissue in the adult patient is thought to contribute to the pathophysiology of obstructive sleep apnea. The underlying etiology of lingual tonsil hypertrophy (LTH) in the adult patient is unclear and likely multifactorial. Previous studies have suggested that the lingual tonsils may undergo compensatory hyperplasia post-tonsillectomy in children, although it is unknown if this occurs or persists into adulthood. The purpose of this study was to determine what factors are associated with LTH in a population of Canadian adults. Methods Adult patients presenting for consultation to an academic Rhinology/General Otolaryngology practice were eligible for enrollment. Demographic data including age, body mass index (BMI), Reflux Symptom Index (RSI), history of allergy, and history of tonsillectomy was collected via questionnaire. Endoscopic photographs of the base of tongue and larynx were captured. These were graded for LTH and Reflux Finding Scale (RFS) by blinded examiners. Statistical analysis was performed by comparing the mean LTH value to the variables of interest using two-tailed T-test. P < .05 was considered significant. Results One hundred two subjects were enrolled. Age ranged from 18 to 78. 28 patients had previous tonsillectomy. This was not associated with a significant increase in lingual tonsil tissue (r = −0.05, p = 0.61). RFS >7 or RSI >13 was considered positive for laryngopharyngeal reflux. There was no difference in LTH based on RSI positivity (p = 0.44). RFS positivity correlated with increased lingual tonsil tissue (p < 0.05). BMI >30 was associated with increased lingual tonsil hypertrophy (p < 0.05). Conclusions An elevated body mass index and positive Reflux Finding Score are associated with lingual tonsil hypertrophy in adults. Reflux symptom index, history of allergy and history of childhood tonsillectomy are not associated with LTH.